Amylopectin from Glutinous Rice as a Sustainable Binder for High‐Performance Silicon Anodes. Issue 2 (8th November 2020) - Ling, Han Yeu; Wang, Chengrui; Su, Zhong; Chen, Su; Chen, Hao; Qian, Shangshu; Li, Dong‐Sheng; Yan, Cheng; Kiefel, Milton; Lai, Chao; Zhang, Shanqing
Abstract : Silicon (Si) has been investigated as a promising anode material because of its high theoretical capacity (4200 mAh g ‐1 ). However, silicon anode suffers from huge volume changes during repeated charge–discharge cycles. In this work, inspired by a remarkable success of the glutinous rice mortar in the Great Wall with ca. 2000‐year history, amylopectin (AP), the key ingredient responsible for the strong bonding force, is extracted from glutinous rice and utilized as a flexible, aqueous, and resilient binder to address the most challenging drastic volume‐expansion and pulverization issues of silicon anode. Additionally, the removal of toxic N‐methyl‐2‐pyrrolidone (NMP) organic solvent makes the electrode fabrication process environmentally friendly and healthy. The as‐prepared Si‐AP electrode with 60 wt% of Si can uphold a high discharge capacity of 1517.9 mAh g −1 at a rate of 0.1 C after 100 cycles. The cycling stability of the Si‐AP has been remarkably improved in comparison with both traditional polyvinylidene fluoride (PVDF) and aqueous carboxymethylcellulose (CMC) binders. Moreover, when the content of silicon in the Si‐AP electrode increases to 70 wt%, a high discharge capacity of 1463.1 mAh g −1 can still be obtained after 50 cycles at 0.1° C. These preliminary results suggest that the sustainably available and environmentally benign amylopectin binders could be a promising choice for the construction of highly stable silicon anodes. Abstract : Inspired by a success of glutinous rice mortar in the Great Wall, amylopectin which could provide strong bonding force was utilized as a flexible, aqueous, and resilient binder to construct highly stable silicon anode for high‐performance lithium‐ion batteries.